Ridge waveguides and passive microwave components - Helszajn, J. (Joseph) (Institution of Engineering and Technology, 2000)
The following topics are dealt with: rectangular waveguides; transverse resonance; finite element method; circular polarisation; dielectric loaded ridge waveguides; Faraday rotation; gyromagnetic quadruple ridge waveguide; ridge cross-guide directional coupler; directly coupled filter circuits; immittance inverters; ridge waveguide filter; mode matching; nonreciprocal ridge isolators; phase-shifters; finline waveguide; inverted turnstile finline junction circulator; semitracking ridge circulator; variational calculus; and Rayleigh-Ritz procedure.